2015
DOI: 10.1080/13854046.2015.1005678
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Competency Restoration: Using the RBANS to Predict Length of Stay for Patients Deemed Incompetent to Stand Trial

Abstract: Intact cognition is a foundational component of one's ability to be competent to stand trial. Given the cost of assessing and treating incompetence, it is recommended that clinicians develop efficient methods to identify individuals who are most likely to require intensive competence-related treatment interventions. This study sought to ascertain whether a brief cognitive screening instrument, the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), could predict the length of stay requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Only individuals who “pass” in-depth performance validity and/or symptom validity assessments are referred for neuropsychological assessment; subsequently, lowering the base rate of malingering behavior present in the current sample and allowing the focus to remain on performance validity. Additionally, Toofanian Ross et al (2015) demonstrated that genuine cognitive impairment due to dementia, did not evidence a significant relationship with hospital LOS. Other studies demonstrated that individuals with dementia were significantly less likely to achieve trial competency (Morris & Parker, 2009), as were individuals with a psychotic disorder (Morris & Parker, 2008).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Only individuals who “pass” in-depth performance validity and/or symptom validity assessments are referred for neuropsychological assessment; subsequently, lowering the base rate of malingering behavior present in the current sample and allowing the focus to remain on performance validity. Additionally, Toofanian Ross et al (2015) demonstrated that genuine cognitive impairment due to dementia, did not evidence a significant relationship with hospital LOS. Other studies demonstrated that individuals with dementia were significantly less likely to achieve trial competency (Morris & Parker, 2009), as were individuals with a psychotic disorder (Morris & Parker, 2008).…”
Section: Methodsmentioning
confidence: 95%
“…Cognition has also been identified as a significant predictor in determining one’s competence to stand trial (Nestor et al, 1999; Toofanian Ross et al, 2015; A. J.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous reports of the RBANS PVTs (Bailie et al, 2012;Bayan et al, 2018;Moore et al, 2013;Morra et al, 2015;Toofanian Ross et al, 2015;Williams et al, 2020), we expect that about 20% of the participants will have scores exceeding the PVTs cutoffs. We assume that BRIEF-A scores suggesting problems with motivation and interest will be comparable (i.e., about 40%) to findings from other studies describing the prevalence of problems with motivation in schizophrenia spectrum disorders (Patel et al, 2015;Rabinowitz et al, 2013;Schennach et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The RBANS allows for the concurrent assessment of cognitive deficits and motivational problems in patients with schizophrenia spectrum disorders. The frequencies at which patients with schizophrenia exceed cutoffs on RBANS PVTs have been examined for some, but not all, possible PVTs deriving from the battery, and have ranged from 9-24% (Bailie et al, 2012;Bayan et al, 2018;Moore et al, 2013;Morra et al, 2015;Toofanian Ross et al, 2015;Williams et al, 2020). No previous study has reported the frequencies of BRIEF-A scores indicating problems with motivation and interest in patients with schizophrenia disorders.…”
Section: Introductionmentioning
confidence: 99%